RATLARDA KARIN FITIKLARININ TEDAVİSİNDE SENTETİK EMİLEBİLEN VE EMİLMEYEN MESH VE TZP İLE KAPLI FORMLARININ KARŞILAŞTIRILMASI - YILDIRIM, ALPEREN (Fırat Üniveristesi, 2024)
Fıtık, tarih boyunca hem insan hekimliğinde hem de veteriner hekimlikte en çok karşılaşılan ve tedavisi üzerinde bilim insanlarının sürekli olarak düşündüğü cerrahi bir lezyondur. Veteriner hekimlikte karın fıtıkları defekt çapının boyutuna bağlı olarak basit cerrahi sütürle kapatılabileceği gibi daha büyük boyuttaki defektlerin kapatılması için organik ya da sentetik greftlerden yararlanılmaktadır. Sentetik greftler kolay elde edilmesi ve uygulama pratikliği yönünden en fazla kullanılan materyallerdir. Sentetik materyallerin en büyük sorunu nüks ve karın içi adhezyonlardır. Bu çalışma karın fıtıklarının tedavisinde emilen ve emilmeyen sentetik meshlerin TZP ile kaplandığında adhezyonu engelleme ve defekt bölgesindeki yara iyileşmesi üzerine yararlı olup olmadığını değerlendirmek amacıyla yapılmıştır. Çalışma materyalini, 250-300 gr ağırlığında 42 adet Spraque Dawley dişi ratlar oluşturdu. Ratlar eşit sayıda ve rastgele olacak şekilde; 6 gruba ayrıldı grup 1; emilen mesh, grup 2; emilen mesh+TZP, grup 3; emilmeyen mesh, grup 4; emilmeyen mesh+TZP, grup 5; kontrol olarak ayrıldı ve bu grupta defekt bölgesi basit ayrı dikişlerle kapatıldı. Grup 6; bu gruptaki hayvanlar TZP elde etmek için kullanıldı. Ratlar rompun–ketalar anestezisine alındıktan sonra karın bölgesi tıraş edilip, povidon iyot ile dezenfekte edildi. Median hattan olacak şekilde deri insizyonu yapıldı. Deri, deri altı bağ dokusu ve kaslar geçildikten sonra karın boşluğuna girildi. Defekt alanı 1x2 cm boyutunda genişletildi. Birinci gruptaki ratların defekt alanı inlay olarak emilen mesh ile, ikinci gruptaki ratlar TZP kaplı emilen mesh ile, üçüncü gruptaki ratlar emilmeyen mesh ile ve dördüncü gruplardaki ratlar da TZP ile kaplı emilmeyen mesh ile kapatıldı. Beşinci gruptaki ratlar kontrol grubu olup, bu gruptaki ratların defekt bölgesi basit ayrı dikişler ile kapatıldı. Tüm dikişler ve derinin kapatılmasında emilmeyen ip kullanıldı. 20 günlük bir takip süresi içinde herhangi bir komplikasyon gelişmedi. Yirminci günün sonunda tüm gruplardaki ratlar CO2 gazı ile ötenazi edildi. Karın boşluğundaki gerilimi ölçmek için patlatma deneyi yapıldı. Bu deneyin sonucuna göre gerilim kuvveti en yüksek dördüncü grupta tespit edildi. Daha sonra karın bölgesi açılarak adhezyon yönünden değerlendirmeler yapıldı. Bu gözlem sonucunda kontrol grubunda daha az olmak üzere mesh kullanılan tüm gruplarda orta ve ileri düzeyde yapışmalar gözlendi. Çekme koparma deneyi, histopatolojik ve biyokimyasal muayeneler yapmak için doku örnekleri alındı. Çekme koparma deney sonucuna göre gruplar arasında istatiksel olarak anlamlı bir fark tespit edilemedi. Histopatolojik bulgular açısından en iyi sonuçlar dördüncü grupta gözlendi. Bu grupta mononükleer hücre infiltrasyonları ile ödem hafif düzeyde görülürken, anjiyogenez orta düzeyde görüldü. Biyokimyasal analizler sonucunda ise emilmeyen mesh ve TZP kullanılan grupta lipid peroksidasyon düzeylerinin ve antioksidan enzim aktivitelerindeki değişimin oksidanlar lehine olduğu ve oksidatif stresi azalttığı görüldü. Sonuç olarak emilmeyen meshin TZP ile kaplanarak kullanılmasının adhezyonu engellemediği ancak neovaskülarizasyonu artırarak yara iyileşmesini hızlandırdığı görüldü. Bu nedenle karın defektlerinin erken dönemde kapanması istendiğinde emilmeyen meshin TZP ile kaplanarak kullanılmasının uygun olacağı kanısına varıldı.

Hernia is a surgical lesion that has been one of the most common issues in both human and veterinary medicine throughout history, with scientists constantly pondering its treatment. In veterinary medicine, abdominal hernias can be closed with simple surgical sutures depending on the size of the defect, while larger defects may require the use of organic or synthetic grafts for closure. Synthetic grafts are the most preferred materials due to their ease of availability and application. The biggest issue with synthetic materials is recurrence and intra-abdominal adhesions. Various barrier methods have been tried to prevent these complications, but the results have been unfavorable. It has been suggested that PRP (Platelet-Rich Plasma) may be effective in preventing these complications; however, apart from wound healing, no additional contribution has been observed. This study was conducted to evaluate whether PRP coating on absorbable and non-absorbable meshes used in the treatment of abdominal hernias could prevent adhesion and promote wound healing in the defect area. The material consisted of 42 female Sprague Dawley rats weighing 250-300 grams each. The rats were randomly divided into six groups of equal numbers: Group I received absorbable mesh, Group II received absorbable mesh+PRP, Group III received non-absorbable mesh, Group IV received non-absorbable mesh+PRP, Group V served as the control, where the defect area was closed with simple interrupted sutures, and Group VI consisted of animals used to obtain PRP. After being anesthetized with rompun-ketalar, the abdominal area of the rats was shaved and disinfected with povidone iodine. A midline skin incision was made along the median line. After passing through the skin, subcutaneous tissue, and muscles, the abdominal cavity was entered. The defect area was enlarged to a size of 1x2 cm. In the first group, the defect area of the rats was closed with an absorbable mesh as an inlay. Rats in the second group were closed with a non-absorbable mesh and its PRP-coated form. Rats in the third group were closed with a non-absorbable mesh, while rats in the fourth group were closed with a non-absorbable mesh coated with PRP. The rats in the fifth group were selected as the control group, and the defect area of these rats was closed with simple interrupted sutures. Non-absorbable sutures were used for all suturing and closure of the skin. Within a 20-day follow-up period, no complications developed. On the twentieth day, all rats in the groups were euthanized using CO2 gas. A burst experiment was conducted to measure the tension in the abdominal cavity. According to the results of the experiment, the highest tensile strength was observed in the fourth group. Subsequently, the abdominal area was opened, and evaluations were made regarding adhesion formation. As a result of this observation, moderate to severe adhesions were observed in all groups where mesh was used, with fewer adhesions noted in the control group. Tensile strength testing was conducted, and tissue samples were taken for histopathological and biochemical examinations. According to the tensile strength test results, there was no statistically significant difference between the groups. The best results in terms of histopathological findings were observed in the fourth group. In this group, mild levels of mononuclear cell infiltration and edema were observed, while angiogenesis was seen at a moderate level. According to the biochemical analysis, it was observed that in the group where non-absorbable mesh and PRP were used, the levels of lipid peroxidation and the changes in antioxidant enzyme activities favored oxidants, reducing oxidative stress. In conclusion, it was observed that using non-absorbable mesh coated with PRP did not prevent adhesion but accelerated wound healing by increasing neovascularization. Therefore, it was concluded that using non-absorbable mesh coated with PRP would be appropriate when early closure of abdominal defects is desired.
Comparison of synthetic absorbable and non-absorbable meshes coated with platelet-rich plasma (PRP) in the treatment of abdominal hernias in rats
Keywords: Veteriner Hekimliği